Conocimiento como reconocimiento en el pensamiento místico-filosófico de la India: una comprensión intercultural a partir del pensamiento de Raimon Panikkar - Cadavid Ramírez, Lina Marcela de la Milagrosa (2023)
The main goal of this article is to develop the concept of knowledge as it is known in a mystic dimension based on philosophical perspective of Raimon Panikkar. An intercultural debate is proposed here, among some of the mystic trends from India, providing an adequate conceptual in order to understand the meaning of the statements of this mystic thinker on his reasoning. The debate proposed here, also has a second goal; to present an analysis on the necessity that mystic experience turn back to the world of western life culture, thus this experience will cease being treated as an usual; strange to our culture occurring only in a minority of the population left out apart from mainstream society.